Stock Management for Sustainable Urban Regeneration - Fujino, Yozo (Springer, 2017)
While the development of material civilization and industrialization initiated by the Industrial Revolution in the eighteenth century made possible a more comfortable life for mankind, it caused a concentration of human resources and led to rapid urbanization around the world. Consequently, a multitude of environmental problems such as global warming, disruption of the e- system, depletion of natural resources, and the accumulation of waste have become international issues. Urbanization accelerated the construction of super high-rise buildings, huge complex facilities, and stacked-up networks of roads and railways. At the same time, however, it resulted in crowded city blocks that were fragile and vulnerable to natural disasters such as ear- quakes, tsunamis, and floods, and in historical structures becoming ruined and cultural urban space exhausted. Maintenance and repair of the amassed stock of structures are causing an economic burden today (...)